ANALISIS KEBIJAKAN PIDANA PADA TINDAK PIDANA PEMBUNUHAN DALAM KEADAAN MABUK - Teguh Apriyanto; Eko Soponyono; Umi Rozah (RechtIdee, 2022)
Criminal liability is only imposed on legal subjects who according to law can be held accountable. This study aims to conduct a juridical analysis and study of the problem, how to assess the crime of murder committed by drunk people. The research method used in this research is normative juridical using secondary data sourced from literature studies. Based on the analysis and study in this study, it is known that drunken murder has not been regulated with certainty in the main regulations of criminal law, namely the Criminal Code (KUHP), but based on the interpretation of the judge in his decision on the criminal case of drunken murder, perpetrators are still punished. The conviction of the perpetrator was based on the consideration that there were two criminal acts that he was charged with, namely the crime of drinking alcohol and the crime of murder. The development of criminal law in the future is expected to provide an explanation regarding the crime of murder in a drunken state.